Notes on Early Land Plants Today. 66. Nomenclatural notes on Acrobolbaceae - Briscoe, Laura; Engel, John; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2015)
The liverwort family Acrobolbaceae Hodgson (1962: 117) is primarily distributed in the Southern Hemisphere and is currently described as containing three subfamilies and seven genera with approximately 60 accepted species names. The subfamily Acrobolboideae (or Acrobolbaceae s. str.) has historically contained the genera Acrobolbus Gottsche et al. (1844: 5), Marsupidium Mitt. in Hooker (1867: 751), and Tylimanthus Mitt. in Hooker (1867: 751).